Мистецтво тлумачення Святого Письма у перекладацьких коментарях С. Аверинцева - Мусієнко, В.П. (Мовознавство, 2012)
У статті запропоновано змістову типологію мовних елементів, які тлумачаться в коментарях С. Аверинцева до здійсненого ним перекладу Святого Письма. Показано, що тлумачення спрямовані на руйнування мовного, культурно-історичного та теологічного бар’єрів; встановлено принципи історичності, традиційності, діалогу, варіативності і межі тлумачення, якими керується С. Аверинцев; розглянуто прийоми пояснення темних місць Святого Письма. The article represents substantial typology of language units which are interpreted in the Commentaries
to Holy Writ by S. Averintzev. It is shown that the ways of interpretation are aimed at the destruction
of linguistic, cultural, historical and theological barriers, appearing in the process of understanding
the text. It is defined that the choice of interpretations is caused by objectives of translation.
It is shown that the methodological basis of interpretation includes the principles of historicism,
dialog, variability and limit Holy Writ.